The missing sink - quantification, categorisation and sourcing of beached macro-debris in the Scottish Orkney Islands. (August 2020) - Buckingham, J.; Capper, A.; Bell, M.
Abstract: Around the coastline of the UK, macro-debris has been observed in average densities of over 700 items per metre. Systematic beach-cleans were conducted at 35 sites around the Scottish Orkney Islands, in order to quantify and categorise the level of marine debris found there. Litter was collected from 100 m transects and categorised by its material, broad source (terrestrial or marine) and potential sector source. Variation between sites, and the relative contribution of pre-determined environmental variables in influencing said variation, were analysed using the "capscale" function for a canonical analysis of principle coordinates (CAP). 513 items/m were observed, (77% plastic), with "String/cord (<1cm diameter)" being the most abundant and widely distributed litter type. 47% of macro-debris was attributed to the fishing sector and < 10% to leisure, living and tourism-associated activities. Conversely, the unique regional hydrodynamics must be examined further, before the source of any given item can be categorically assigned. Highlights: The composition of macro-debris found on beaches in the Scottish Orkney Islands is examined 513 items/100m of coastline were collected, higher than the Scottish national average in the same year The largest sectoral contributor to beached debris in the region was fisheries Site accessibility, beach aspect and the distance to the nearest port were the strongest statistical explanatory factors